ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP KEBERLANGSUNGAN PEMBELAJARAN SISWA DI SEKOLAH DASAR KABUPATEN KEDIRI - Santi, Novi Nitya; Laila, Alfi; Khan, Rosa Imani; Iswantiningtyas, Veny; Sahari, Sutrisno (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
This study aims to describe the impact of the Covid-19 pandemic in; 1) Students, 2) Parents, and 3) Teachers on the Sustainability of Learning. The research approach uses descriptive qualitative research. The data source in this study was 202 students, 119 guardians of students, and 33 elementary school teachers in five sub-districts (Puncu, Kandangan, Mojo, Tarokan, and Baiyakan) Kediri Regency. Data collection techniques use quizzes, interviews, and documentation. The Miles and Huberman model uses the data analysis technique with data reduction measures, data presentation, and conclusion withdrawal. The results showed that; 1) Students are finished at the decline in competencies and characters that have been formed in face-to-face learning activities in schools in the form of learning outcomes, discipline, power, and learning interest that tend to be faster, understanding and completeness of learning outcomes, learning concentration, the intensity of guidance and Consult with Teacher also students. 2) Diversity background guardians of students in terms of education, age, work, income, experience, social and competence greatly affect the sustainability, assistance, and learning outcomes of children. Many students who are less successful in holding a baton from the teacher are caused by the diversity of the background possessed. 3) Inflanganization of infrastructure and facilities is a major obstacle for teachers in developing online learning for their students. This has an impact on children's motivation and learning outcomes during online learning in the Pandemic Covid-19 period. The results of this study are very important as the basis for improving further education quality.